Amos and Hosea. A contribution to the problem of the 'Profetenschweigen' in the Deuteronomistic History (Dtr) - Wittenberg, Gunther (Old Testament essays, 1993)
The question why the Deuteronomisic History does not mention Amos and Hosea, although prophets play such a great role in the overall theological plan of the work, has baffled Old Testament scholars. The solutions proposed by Noth, Koch, and Criisemann are not satisfactory because they try to explain the omission from the perspective of an exilic origin of the Deuteronomistic History. A pre-exilic setting during the time of Josiah, as proposed by Cross and Nelson, offers a more plausible context. A minority movement which Lang calls the ""Yahweh-alone movement', in opposition since the time of Elijah, had now become the victorious party in Judah. The message of the prophets, particularly of Hosea, had strongly influenced the movement from its origin, culminating in the legislation of Deuteronomy. But during the final years of Josiah Amos' radical message of doom and Hosea's rejection of the institutition of kingship was no longer acceptable. The Deuteronomistic historian therefore omitted them from his work.